2010
DOI: 10.3109/02841860903575273
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer recurrence risk related to concurrent use of SSRI antidepressants and tamoxifen

Abstract: (2010) Breast cancer recurrence risk related to concurrent use of SSRI antidepressants and tamoxifen, Acta Oncologica, 49:3, 305-312,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 24 publications
5
69
0
3
Order By: Relevance
“…Although some studies have reported an association between antidepressants and the risk of breast cancer (Lawlor et al, 2003;Lash et al, 2010), other preclinical studies indicate that antidepressants display anticancer activities (Xia et al, 1999;Coogan et al, 2009;Cloonan and Williams, 2011). These discordant observations may relate to the activity of the individual antidepressants.…”
Section: Discussionmentioning
confidence: 54%
“…Although some studies have reported an association between antidepressants and the risk of breast cancer (Lawlor et al, 2003;Lash et al, 2010), other preclinical studies indicate that antidepressants display anticancer activities (Xia et al, 1999;Coogan et al, 2009;Cloonan and Williams, 2011). These discordant observations may relate to the activity of the individual antidepressants.…”
Section: Discussionmentioning
confidence: 54%
“…The effect of tamoxifen was reduced in patients taking antidepressants resulting in a significantly higher 2-year breast cancer recurrence rate, 13.9% compared to 7.5% in patients not taking antidepressants with tamoxifen (HR 1.92, 95% CI 1.33-2.76, p < 0.001) [277]. In contrast to these findings, many studies suggest no association between antidepressants and breast cancer recurrence, even though this contradicts the biology [258,272,278,279]. Reasons for this inconsistency in previous studies include differences in SSRI inhibition ability, genomic differences, differences in data collection, limited information on tamoxifen compliance, and small sample size [274].…”
Section: Antidepressant Usementioning
confidence: 98%
“…Since SSRIs inhibit cytochrome P-450 2D6 (CYP2D6), the enzyme that metabolizes tamoxifen, they decrease the amount of tamoxifen metabolites in the blood [272]. Some SSRIs inhibit CYP2D6 more than others.…”
Section: Antidepressant Usementioning
confidence: 99%
See 2 more Smart Citations